Waste Treatment Design at Sugar Factory - Munawar Ali; M. T. Safirin (International Journal of Science and Society, 2022)
Waste is a by-product resulting from a process. Waste if disposed of freely without prior processing can harm the surrounding environment. Proper waste management makes waste more friendly to the environment. There are even several categories of waste that can be reused. A sugar factory is a company that processes sugar cane into crystal sugar that can be used for cooking. At the sugar factory, there are problems that occur, namely the absence of waste processing that is produced as a by-product of the production process. Therefore, in this research, the design of by-products of the sugar production process is carried out. after the waste treatment design was made in the sugar factory, parameters such as pH, BOD, COD, TSS, Oil and Fat, Sulfide, which was previously harmful to the environment, has met quality standards after processing.